Planning for Iteration-Focused User Experience Testing in an Academic Library - Gallant, Jeffrey; Wright, Laura (Taylor and Francis, 2014)
Many case studies and literature reviews focus on usability or user experience testing in libraries, but most are focused on testing before a planned website redesign, and often only include formal usability tests. This article contains an updated literature review on iteration-focused user experience test planning in academic libraries, followed by a description of the implementation of a user experience testing plan at Valdosta State University's Odum Library and its use in a Campus Information Technology redesign of the library website.
All figures in the preprint are in the Figures PDF with captions.
Keywords: usability, user experience, academic library, iteration, testing, ux, heuristics